Airborne geophysical data from the Queen Elizabeth Islands, Canadian Arctic, 2014 - Benham, Toby; Christoffersen, Poul; Dowdeswell, Julian; Siegert, Martin (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Survey flying (using Basler BT-67 aircraft C-GJKB) was carried out between 1 May 2014 and 12 May 2014 to measure the ice thickness, surface elevation and magnetic anomaly of the Queen Elizabeth Islands, Nunavut, Canada. The primary radar instrument was the UTIG-JPL High-Capability Radar Sounder (HICARS: Peters et al., 2005). Level 1 radar data products are hosted at NSIDC. Surface elevation data was acquired by a fixed beam Riegl laser altimeter using a solid-state infrared lasar firing at 100 Hz. A tail boom-mounted cesium vapor total field magnetometer specially configured for the aircraft measured the magnetic anomaly. Funding was provided by NERC grants NE/K004999/1, NE/K004956/1 and NE/K004956/2. : The lineage of the data is discussed in the field report and further data descriptions written by the project team, These are included in this dataset. : Survey flying was undertaken using Basler BT-67 aircraft C-GJKB. The primary radar instrument was the UTIG-JPL High-Capability Radar Sounder (HICARS: Peters et al., 2005). HICARS is a phase-coherent, frequency-chirped radar with a 60 MHz centre-frequency (VHF) and 15 MHz of bandwidth operating with a pulse repetition frequency of 6400 Hz and transmitting a peak power of 8 kW using an amplifier/antenna system developed by the Technical University of Denmark (TUD). Surface elevation data was aquired by a fixed beam Riegl laser altimeter using a solid-state infrared laser firing at 100 Hz. This laser altimeter has been flying as part of the UTIG instrument suite since 2004 and routinely achieves elevations accurate to better than 10 cm (Young et al., 2008). A tail boom-mounted cesium vapor total field magnetometer specially configured for the BT-67 was carried throughout the survey. The system included aircraft field compensation provided by a belly-mounted fluxgate magnetometer. : The quality of the data is discussed in the field report and further data descriptions written by the project team, These are included in this dataset.